Prevalence of Cystic Echinococcosis Genotypes in Iranian Animals: A Systematic Review and Meta-Analysis - Sahar Khodashenas; Mehran Akbari; Reza Beiranvand; Mojtaba Didehdar; Mohammad Shabani; Parnia Iravani; Behnam Abedi (Journal of Parasitology Research)
Background. Cystic echinococcosis is considered a public health problem that if left untreated can have dangerous consequences for the person. The disease is caused by Echinococcus granulosus sensu lato larvae. The main risk factors for this parasitic infection are habitat, direct contact with dogs, use of raw vegetables, and use of unwashed vegetables. The most important factors affecting the prevalence of HCD are economic, occupational, agricultural, educational, and factors related to public health and cultural habits of the general public in that geographical area. Objectives. The purpose of this study was to investigate the prevalence of the types of cystic echinococcosis genotypes (E. granulosus sensu stricto (G1-G3) and E. Canadensis (G6 and G7)) in livestock in Iran. Method. This systematic review was conducted, using Medline/PubMed, Scopus, Web of Sciences, and Google Scholar databases, to identify studies of cystic echinococcosis in animals published from 2010 to April 14, 2021. Finally, 28 studies were selected for meta-analysis, which was analyzed using Stata software version 14. The cystic echinococcosis prevalence with 95% confidence intervals of animals was synthesized using the random effect model. Heterogeneity was evaluated and in cases where the I2 index was higher than 75%, subgroup analysis was performed according to the types of animals. Result. The highest prevalence of cystic echinococcosis infection was related to G1 genotype (P=0.91 (95% CI=0.84,0.97)) and the prevalence was related to G2 genotype (P=0.07(95% CI=0.00,0.18)). The results of the subgroup analysis showed that in the G1 genotype the highest prevalence was observed in Goats and Buffaloes with P=1 (95% CI=0.96,1) and P=1 (95% CI=0.97,1), in the G3 and G6 genotypes the highest prevalence was observed in camels with P=0.50 (95% CI=0.31,0.69), and P=0.45 (95% CI=0.22,0.69), respectively. Conclusion. The cystic echinococcosis genotypes vary from region to region or from country to country and also from host to host, and according to the results, it should always be stopped in areas where the prevalence of such genomes suitable for livestock as well as human food sources to prevent infection of livestock and thus human exposure to cystic echinococcosis.